Tratamiento por Deshidratación y Acondicionamiento Químico a los lodos generados en el Proceso de Potabilización de las aguas para reducir su carga, Moyobamba, 2014 - Gutierrez Cubas, Roymer (2015)
The study checks the efficiency of the proposed treatment (Conditioning Chemical and drying beds), to reduce the volume of the sludge generated in plants Water treatment plants by applying these treatment methods. As These are currently generating an environmental problem that mainly affects Bodies of water, since they usually receive the majority of the waste that they Generate factories, processing plants, among others, and these sludge are no exception. In order to be able to apply chemical conditioning and sludge dehydration, To carry out laboratory and field work. In the laboratory parameters were determined Of the sample (pH, Total Suspended Solids and Turbidity), the optimum dose of polymer Cationic (CAT FLOC 8103) for the chemical conditioning and the percentage of Removal of sludge. In the field, the sludge was chemically conditioned by applying the Dose of cationic polymer obtained in the laboratory and the percentage of Removal of sludge. For dehydration, the conditioned sludge was discharged into The drying beds of 1.8 m x 1.2 m, which had as a means of drainage a layer of sand (E = 0.10 m) and gravel (e = 0.30 m), and the percentage of sludge removal was calculated. To the At the end of the treatment, a sample of filtered water was extracted from each of the beds Of drying to be able to determine the values ​​of the evaluated parameters: pH, Solids Totals Suspended and Turbidity. The results obtained showed that it is feasible to reduce the volume by 48.07% Sludge to be disposed of through the application of chemical conditioning and Dehydration through the drying beds this was reduced to 57.81%. It was also verified that with the application of chemical conditioning and Dehydration as treatment its pollutant load was reduced from the following PH of 15.19%, total solids in suspension at 78.10% and 96.41%, being the parameters evaluated in the present research work.